THE IMPACT OF UPPER AIRWAY DISORDERS ON CRANIOFACIAL DEVELOPMENT IN CHILDREN: A NARRATIVE REVIEW - Kędrak, Magdalena; Miśkiewicz, Emilia; Wieczorek, Zofia; Stanisławski, Dominik; Stopa, Ewa; Borek, Natalia; Gałązka, Julia; Jabłońska, Wiktoria; Krupa, Hanna; Pochwalski, Jakub (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Upper airway disorders in children represent significant clinical problems that may profoundly affect craniofacial development. These conditions disrupt natural breathing patterns and trigger compensatory mechanisms that may lead to permanent structural and functional changes in the developing craniofacial complex. Aim: The aim of this narrative review was to evaluate the impact of upper airway disorders on craniofacial development in children. Material and methods: A narrative review was conducted using PubMed/MEDLINE and Google Scholar. A purposive, non-systematic approach was used for article selection, and a total of 23 publications were included based on clinical relevance. Results: Upper airway disorders were associated with measurable craniofacial transformations beginning early in development. Increased vertical facial dimensions, altered sagittal skeletal relationships, and a higher prevalence of malocclusion, including anterior crossbite were the most common changes. Untreated conditions result in permanent structural abnormalities, dental health problems, and systemic complications including cognitive deficits and cardiovascular issues. Conclusions: Early diagnosis and multidisciplinary management of upper airway disorders are essential to prevent long-term structural, functional, and systemic complications.